Network of Retail Developing for Sustainable Growth of Thai Small Retail Business - Sutthitham, Nupartpat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purpose of the “Network of Retail Developing for Sustainable Growth of Thai Small Retail Business” research is to study the development structure problems and obstacles of consumer goods distribution to Thai retail store additionally to find key success factors of network developing for Thai retail business and finally to propose appropriate of Network of Retail Developing for Sustainable Growth of Thai Small Retail Business. This qualitative research is investigated from relevant documents and in-depth interview of the key informants consisting of distributor owners of Proctor and Gamble Trading (Thailand) - P&G, Johnson & Johnson consumer (Thai), Dumex, academic experts and government that expert in logistics. This network can be applied practically. Article history : Accepted 5 February 2016 SIMILARITY INDEX = 3.26